Awareness Of The Risks Associated With Smoking Can Decrease E-Smoking Behavior In The City Of Jambi - Adinda Salsa Egidea; M.Ridwan; Vinna Rahayu Ningsih (Jurnal EduHealth, 2024)
Smokers Switch to E-Cigarettes in Jambi City in 2024, namely there is a relationship between the variables of friend influence, advertising and social media support, as well as the behavioral knowledge of tobacco smokers switching to e-cigarettes in Jambi City. Indonesia occupies the fifth position as a producer of tobacco leaves and the third position globally in cigarette consumption. The level of distribution of cigarettes across the country has reached. Technological developments have brought a new phenomenon in the form of tobacco cigarette replacements, such as vapor, vape and e-cigarettes, which are considered an effort to help smokers quit smoking habits, especially in the Jambi city area. This study aims to be Factors Related to the Behavior of Conventional Smokers Who Switch to E-Cigarettes in Jambi City in 2024. The type of research used is a cross sectional approach. The sample for this study was 96 people. The sampling technique used is Accidental Sampling. The population in this study is all individuals who use electronic cigarettes (vapes). The results of this study found that there was a relationship between the influence of friends and the behavior of tobacco smokers to e-cigarettes (p-value: 0.001), the relationship between advertising support and social media, the behavior of tobacco smokers to e-cigarettes (p-value: 0.001), and the relationship of knowledge with the behavior of tobacco smokers to e-cigarettes (p-value: 0.026) in Jambi City. Factors related to conventional behavior